"Active" hydroponic greenhouse system to kick-start and augment reforestation program through carbon sequestration – an experimental and theoretical feasibility study. (15th August 2016) - Ku, Harn Wei; Tok, Chuan Tiong; Suresh, Aruna; Ong, Boon Lay
Abstract: Besides promoting biodiversity, a reforestation program plays an important role in carbon capture and sequestration. However, the need to develop tree saplings well before they can be deployed on reforestation sites can delay the start of the sequestration process. This study proposed a way to reduce this time wastage by creating and erecting a special hydroponic greenhouse system on the reforestation site, while waiting for the saplings to be ready. While in service, this system makes use of an "active" mode of removing carbon dioxide from distributed and stationary sources, such as onsite generators that are widely used around the world and yet relatively neglected in the carbon capture and sequestration literature. Experimental tests and theoretical modeling of a hypothetical scaled-up version of the hydroponic greenhouse system using Ipomoea aquatica Forsk as the "stand-in" plant sequesters showed that this greenhouse system can potentially remove an amount of carbon dioxide equal to what fully grown water oak trees occupying the same land area can remove, but in a much shortr time. That is, this greenhouse system can kick-start and augment the sequestration function of the reforestation program. The methodology described in this study can be applied to determine appropriate "stand-in" plants for any kind of tree species that are selected for a reforestation program. Graphical abstract: Highlights: Ipomoea aquatic Forsk is grown in a hydroponic greenhouse (HGh). Exhaust gas containing CO2 is directed into HGh. The plants were found to remove CO2 at rates equivalent to some growth trees. HGh can thus kick-start a reforestation project before the saplings are ready. Enhanced C removal means HGh can augment the CCS of reforestation project.